The mediating role of children’s self-concept on the relationship between early language delay and depression during pre-adolescence - Ting, Sharon (2024)
Children with language problems are at risk of poorer self-concepts and experience increased feelings of depression as compared to their typically developing peers. To date, the potential mediating role of children’s self-concept on the relationship between language problems and mental health outcomes has yet to be examined. Utilizing a sample of 326 children (51.5% males) from Singapore’s birth cohort study, we investigated whether the association between children’s early language delay and later depressive symptoms is mediated by their overall self-concept. English language ability was assessed at 4 years using the Peabody Picture Vocabulary Test. Following conventional cut-offs in past studies, children with standardized scores below 1.25 standard deviations from the mean were classified as language delayed (n = 29). Children filled in the Piers-Harris Self-Concept scale at 8.5 years old and the Child Depression Inventory at 10 years old. To test the proposed mediating effect of self-concept, indirect effects were estimated using the bias-corrected bootstrapping method while controlling for child sex. Language delay predicted poorer self-concept (B = -3.19, SE = 1.63, p = .05) and was marginally associated with more severe depressive symptoms (B = 3.56, SE = 1.95, p = .07). A more positive self-concept also predicted less severe depressive symptoms (B = -0.58, SE = 0.07, p < .001). Further, children’s self-concept significantly mediated the relationship between language delay and depressive symptoms (B = 1.84, SE = 0.98, 95% CI [.01, 3.83]). Together, findings emphasize the importance of fostering positive self-concepts in children with language delays to mitigate the risk and severity of depression during adolescence.